Coating and preparation method thereof
By combining resins such as modified epoxy acrylate and aromatic polyurethane acrylate, coatings with long activation period and low curing energy were prepared, which solved the problems of poor adhesion to pine wood and environmental pollution of PU sealing primer, and achieved the effects of high adhesion, low pollution and high efficiency construction.
Patent Information
- Application Number
- CN202310786294.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-06-29
AI Technical Summary
The existing UV coatings have poor adhesion to pine substrates, easy paint film to fall off and bubble, and the PU sealing primer has problems of environmental pollution and low construction efficiency.
Modified epoxy acrylate and aromatic polyurethane acrylate are used as main resins, and coatings with long activation period and low curing energy are prepared by combining functional monomers, photoinitiators and curing agents, reducing the heating of pine wood during ultraviolet curing, and improving adhesion and stability of the coating film.
It improves the adhesion of the paint to pine wood and oil sealing effect, reduces the curing energy of the coating film, extends the activation period, and reduces the problems of environmental pollution and low construction efficiency.
Smart Images

Figure CN116716004B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coatings, and in particular to a coating and a preparation method thereof. Background Art
[0002] Pine is a durable, easy to obtain, cheap and easy to process wood, which is widely used in construction, furniture, cultural supplies and other industries. At the same time, the oil content in pine is relatively high, especially the knots of Pinus sylvestris contain a lot of oil. When coating pine with paints such as oil or water-based paint, the oil in pine will lead to technical problems such as insufficient adhesive strength, poor adhesion of the paint, and easy blistering and shedding of the paint film.
[0003] In the prior art, the technical problems of poor coating adhesion and blistering and falling off of paint film on pine wood can be solved by degreasing pine wood and using PU closed primer to seal oil on pine wood. However, the degreasing process is relatively cumbersome and slow, so the degreasing method is gradually eliminated by pine furniture factories. Although the method of sealing oil on pine wood with PU closed primer has a good sealing grease effect, the solvent content in PU closed primer is high, which pollutes the environment and does not meet the national requirements for low volatile organic compounds (VOC) emissions. At the same time, this method also has the problem of low construction efficiency.
[0004] In order to solve the problems of production efficiency and environmental pollution, the prior art also uses UV coatings to seal pine wood with oil. UV coatings use ultraviolet light as a curing energy source. The photoinitiator in the coating absorbs ultraviolet light to form free radicals, which triggers oligomer cross-linking and curing, thereby curing the coating. UV coatings have the advantages of fast curing speed, low VOC emissions, smooth appearance, and full paint film. However, ultraviolet light is often accompanied by infrared light. During the curing process of UV coatings under ultraviolet light, the temperature of the pine wood substrate is increased by infrared light, causing a large amount of pine oil to emerge from the surface of the pine knots of the pine wood substrate, which in turn leads to poor adhesion of the coating to the pine wood substrate, shedding of the paint film, and bubbling. Summary of the invention
[0005] The purpose of the present application is to provide a coating and its application to solve the technical problems of poor adhesion of UV coatings to pine wood substrates, paint film shedding and bulging in the prior art.
[0006] In a first aspect, an embodiment of the present application provides a coating. The coating comprises the following components in parts by weight:
[0007] 40-50 parts of modified epoxy acrylate;
[0008] 10-15 parts of aromatic polyurethane acrylate;
[0009] 16 to 36 parts of functional monomer;
[0010] 3.2-5.4 parts of photoinitiator;
[0011] 5-10 parts of curing agent;
[0012] Wherein, the modified epoxy acrylate is adipic acid modified epoxy acrylate;
[0013] The functional monomer includes at least one of dipropylene glycol diacrylate and tripropylene glycol diacrylate.
[0014] The coating of the embodiment of the present application uses adipic acid modified epoxy acrylate and aromatic polyurethane acrylate as the main resins. By controlling the mass fractions of adipic acid modified epoxy acrylate and aromatic polyurethane acrylate and compounding them with functional monomers, photoinitiators and curing agents, the coating has a long activation period, low curing energy, good coating film toughness, good adhesion to pine wood and good oil sealing effect on pine wood.
[0015] In a second aspect, the present application provides a method for preparing a coating. The method comprises the following steps:
[0016] Provide modified epoxy acrylates, aromatic polyurethane acrylates, functional monomers, photoinitiators and curing agents;
[0017] The materials including modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent are mixed to obtain the coating.
[0018] Among them, the modified epoxy acrylate is 40-50 parts, the aromatic polyurethane acrylate is 10-15 parts, the functional monomer is 16-36 parts, the photoinitiator is 3.2-5.4 parts, and the curing agent is 5-10 parts. The modified epoxy acrylate is adipic acid modified epoxy acrylate; the functional monomer includes at least one of dipropylene glycol diacrylate and tripropylene glycol diacrylate.
[0019] The preparation method of the embodiment of the present application is compounded with adipic acid-modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent, so that the prepared coating has a long activation period and low curing energy. Since the coating prepared by the preparation method of the embodiment of the present application has low curing energy, the infrared light energy in the ultraviolet light during curing is effectively reduced, and the temperature rise of the pine wood during the ultraviolet curing process when the coating is applied to the pine wood is further reduced, which greatly reduces the pine oil secretion on the surface of the pine wood during the ultraviolet curing process of the coating, and improves the adhesion of the coating to the pine wood and the stability of the coating formed by the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0021] Figure 1 A process flow chart of the coating provided in the embodiments of the present application. DETAILED DESCRIPTION
[0022] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0023] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0024] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0025] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0026] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0027] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0028] In a first aspect, this embodiment provides a coating. The coating comprises the following components in parts by weight:
[0029] 40-50 parts of modified epoxy acrylate;
[0030] 10-15 parts of aromatic polyurethane acrylate;
[0031] 16 to 36 parts of functional monomer;
[0032] 3.2-5.4 parts of photoinitiator;
[0033] 5-10 parts of curing agent;
[0034] Wherein, the modified epoxy acrylate is adipic acid modified epoxy acrylate;
[0035] The functional monomer includes at least one of dipropylene glycol diacrylate and tripropylene glycol diacrylate.
[0036] The coating of the embodiment of the present application uses adipic acid-modified epoxy acrylate as the main resin, and is compounded with adipic acid-modified epoxy acrylate, aromatic polyurethane acrylate functional monomer, photoinitiator and curing agent in specific mass fractions, so that the coating has low curing energy, and the formed coating film has good flexibility, good adhesion between the coating film and pine wood, and has excellent oil sealing effect on pine wood, which can effectively prevent pine oil seepage from the surface of pine wood.
[0037] The coating in the embodiment of the present application has low curing energy and can cure quickly under low-energy ultraviolet light irradiation. Since the energy of ultraviolet light is low, the energy of infrared light accompanying the ultraviolet light is low, thereby effectively reducing the problem of the pine wood substrate rising when exposed to ultraviolet light, reducing the exudation of pine oil on the surface of the pine wood substrate, especially reducing the exudation of pine oil on the surface of the pine knot.
[0038] In specific examples, the weight percentage of the modified acrylic resin can be 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 59 parts, 50 parts, which are typical but non-limiting weight percentages.
[0039] In some embodiments, the modified acrylic resin can be Jiangxi Kunlong HM-303. The modified acrylic resin contains carboxyl groups and does not contain residual epoxy groups. The modified acrylic resin of these types is controlled and the quality of the acrylic resin is matched, so that the coating prepared by compounding the modified acrylic resin with aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent has a long activation period, good film toughness, good adhesion to pine wood, and good sealing effect on pine wood.
[0040] In some embodiments, the weight fraction of the aromatic polyurethane acrylate may also be 10 to 15 parts. In specific examples, the weight fraction of the aromatic polyurethane acrylate may be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc., which are typical but non-limiting weight fractions.
[0041] In some embodiments, the aromatic polyurethane acrylate can be at least one of Ketian Chemical 5210 and Jiangxi Kunlong HM316. The aromatic polyurethane acrylate is controlled to be of these types, and the content of the aromatic polyurethane acrylate is combined, so that the aromatic polyurethane acrylate and adipic acid-modified acrylic resin are combined as the main components, and are compounded with functional monomers, photoinitiators and curing agents to form a coating with a long activation period, good film toughness, good adhesion to pine wood, and good pine wood sealing effect.
[0042] The functional monomer may include only one compound, for example, dipropylene glycol diacrylate or tripropylene glycol diacrylate; the functional monomer may also be a mixture, for example, a mixture of propylene glycol diacrylate and tripropylene glycol diacrylate.
[0043] In some embodiments, the functional monomer may further include hydroxyethyl methacrylate. In a further embodiment, on the basis of the functional monomer having a mass fraction of 16 to 36 parts, when the functional monomer includes hydroxyethyl methacrylate, the mass fraction of hydroxyethyl methacrylate may be controlled to be ≤5 parts. In a specific exemplary embodiment, the mass fraction of hydroxyethyl methacrylate may be 0 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, etc., which are typical but non-limiting mass fractions, and the mass fraction of the functional monomer may be 16 parts, 20 parts, 25 parts, 30 parts, 36 parts, etc., which are typical but non-limiting mass fractions.
[0044] Controlling the functional monomers to include these compounds and controlling the mass fraction of these compounds such as hydroxyethyl methacrylate can effectively improve the coating film formed by the coating to have a faster curing time, suitable shrinkage and toughness, and improve the adhesion to pine wood.
[0045] In some embodiments, the photoinitiator may include photoinitiator A and photoinitiator B, wherein photoinitiator A may include at least one of 2-hydroxy-methylphenylpropane-1-one and 1-hydroxycyclohexylphenylketone, and photoinitiator B may include bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. In a specific example, photoinitiator A may be Jiuri New Material JRCure 1103, in which case photoinitiator A is a surface-drying photoinitiator with fast surface drying; photoinitiator B may be Jiuri New Material JRCure 1109, in which case photoinitiator B can promote internal drying of the coating.
[0046] In some embodiments, based on the mass fraction of the photoinitiator being 3.2 to 5.4 parts, the mass fraction of the photoinitiator A can be 3 to 5 parts, and the mass fraction of the photoinitiator B can be 0.2 to 0.4 parts. In specific examples, the mass fraction of the photoinitiator A can be 3 parts, 3.2 parts, 3.5 parts, 3.7 parts, 4 parts, 4.2 parts, 4.5 parts, 4.7 parts, 5 parts, etc., which are typical but non-limiting mass fractions; the mass fraction of the photoinitiator B can be 0.2 parts, 0.3 parts, 0.4 parts, etc., which are typical but non-limiting mass fractions.
[0047] The mass fractions of photoinitiator A and photoinitiator B are controlled to compound photoinitiator A and photoinitiator B, thereby promoting the uniform drying and curing of the coating of the embodiment of the present application during use to form a coating film with good uniformity.
[0048] In some embodiments, the curing agent may include an isocyanate curing agent. In a specific example, the curing agent may be a hexamethylene diisocyanate-based polyisocyanate. In a specific example, the curing agent may include at least one of Wanhua HT-100 and Covestro Desmodur N3300.
[0049] The curing agent is controlled to be these compounds, so that the curing agent is compounded with the main resin, and other components are matched to form a coating with a long activation period, low curing energy, good film toughness, and strong adhesion. In addition, these curing agents can also reduce the oil on the surface of the pine wood substrate during subsequent use after the pine wood substrate is treated with the coating of the embodiment of the present application, reduce the probability of bubbling and shedding of the coating, and improve the stability of the coating.
[0050] These curing agents, such as hexamethylene diisocyanate-based polyisocyanate, contain no organic solvents and have a solid content of 100%, which effectively reduces the emission of organic solvents during the use of the coating.
[0051] The NCO groups contained in these curing agents, such as hexamethylene diisocyanate-based polyisocyanate, can react with COOH in turpentine to form a dense coating to prevent the pine wood substrate from continuing to leak grease during subsequent use. The NCO group also slowly reacts with -OH and -COOH in the coating. The curing agent is UV-cured to form a dense coating, further improving the coating's oil-sealing effect on the pine wood substrate.
[0052] In some embodiments, the coating of the present application embodiment may further include 10 to 20 parts of filler by weight. In further embodiments, the filler may include at least one of talcum powder, titanium oxide, aluminum oxide, and calcium silicate. The addition of these fillers effectively reduces the viscosity of the coating, improves its fluidity and coating performance, and improves the physical and chemical properties of the coating film, such as hardness, wear resistance, impact resistance, and corrosion resistance.
[0053] In some embodiments, the coating of the present application embodiment may further include 0.1 to 0.2 parts by weight of a defoamer. In a further embodiment, the defoamer may include at least one of AIREX 920, Huaxia Additive HX-2620, Huihong Additive HF3022, and Better Chemical Huihong Additive, wherein AIREX 920 is a silicone-free polymer defoamer. These defoamers effectively reduce bubbles on the surface of the coating, making the surface of the coating smooth and uniform.
[0054] In some embodiments, the coating of the present application embodiment may further include 0.2 to 0.5 parts of a dispersant and 0.3 to 0.5 parts of an anti-settling agent by weight. In a further embodiment, the dispersant may include BYK 110; the anti-settling agent may include silicon dioxide and AEROSIL R972. The addition of these dispersants and anti-settling agents effectively improves the dispersion state of particles in the coating, improves the uniformity and stability of the coating, improves the rheological properties of the coating, reduces the difficulty of the coating process, and improves the quality and performance of the coating film.
[0055] In some embodiments, the viscosity of the coating of the present application embodiment at 25°C is 80-120KU. In specific examples, the viscosity of the coating can be 80KU, 90KU, 100KU, 110KU, 120KU, etc., which are typical but non-limiting viscosities. Controlling the viscosity of the coating within this range allows the coating to have good rheological properties, facilitates the coating of the coating, and effectively improves the coating efficiency and uniformity of the coating film.
[0056] In some embodiments, the activation period of the coating of the present application embodiment is ≥24 hours. The activation period of the coating of the present application refers to the mixing validity period of the coating, and its specific meaning refers to the period of time from the mixing of the various components of the coating to the time before it cannot be used. The coating activation period can be a certain time after the coating is mixed. Although the viscosity rises during this time, it does not affect the construction, and has no obvious effect on the film forming process and the coating performance. This time period can be used as the activation period of the coating. The advantage of a long activation period is that more coatings can be prepared at one time, and it can be placed for one night and then continued to be used. As long as the coating is used up within the activation period (e.g., 24h), there will be no waste and quality problems.
[0057] Controlling the activation period of the coating within this range allows the coating to remain stable for a relatively long period of time, effectively improving the coating efficiency of the coating production line and reducing the cost of pine wood coating.
[0058] In some embodiments, according to the standard of GB T 9286-2021, the adhesion of the coating of the embodiment of the present application is level 1 to 2, specifically level 1 or level 2.
[0059] In a second aspect, the present application provides a method for preparing a coating. Figure 1 As shown, the preparation method comprises the steps of:
[0060] Step S01: providing modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent;
[0061] Step S02: Mixing materials including modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent to obtain a coating.
[0062] Among them, the modified epoxy acrylate is 40-50 parts, the aromatic polyurethane acrylate is 10-15 parts, the functional monomer is 16-36 parts, the photoinitiator is 3.2-5.4 parts, and the curing agent is 5-10 parts;
[0063] The modified epoxy acrylate is adipic acid modified epoxy acrylate;
[0064] The functional monomer includes at least one of dipropylene glycol diacrylate and tripropylene glycol diacrylate.
[0065] The coating prepared by the preparation method of the embodiment of the present application has the characteristics of long activation period, low curing energy, fast curing, strong adhesion and good sealing effect on pine wood.
[0066] Step S01:
[0067] The modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent provided in step S01 are the above-mentioned modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent, which are not repeated here.
[0068] In some embodiments, a defoamer, a dispersant, an anti-settling agent and a filler may be provided in step S01. The defoamers, dispersants, anti-settling agents and fillers are the defoamers, dispersants, anti-settling agents and fillers mentioned above, which will not be described in detail here.
[0069] Step S02:
[0070] In step S02, the materials provided in step S01, including the modified epoxy acrylate, the aromatic polyurethane acrylate, the functional monomer, the photoinitiator and the curing agent, are mixed to obtain a coating.
[0071] In some embodiments, while the modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent are mixed, a defoamer, a dispersant, an anti-settling agent and a filler may also be mixed.
[0072] In some embodiments, the mixing process may include the following steps:
[0073] Step S021: performing a first mixing treatment on modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent to obtain a first mixture;
[0074] Step S022: performing a second mixing process on the first mixture and the curing agent to obtain a coating.
[0075] In some embodiments, the first mixture may further include a defoaming agent, a dispersant, an anti-settling agent, and a filler.
[0076] Through the first mixing treatment, modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent are made into a first mixture, and the second treatment is carried out before the paint is used, which avoids the contact between the modified acrylic resin and the curing agent before use and improves the storage stability of the paint.
[0077] The coatings and preparation methods of the present invention are described below by means of a number of specific embodiments.
[0078] Example 1
[0079] This embodiment provides a coating, including modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator, defoamer, dispersant, anti-settling agent, filler and curing agent.
[0080] Among them, the modified epoxy acrylate is adipic acid modified epoxy acrylate, the functional monomer is tripropylene glycol diacrylate, the photoinitiator includes photoinitiator A and photoinitiator B, photoinitiator A is 2-hydroxy-methylphenylpropane-1-one, photoinitiator B is bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, the defoamer is TEGO AIREX 920, the dispersant is BYK 110, the anti-settling agent is Evonik degussa AEROSIL R972, the filler is talc, and the curing agent is hexamethylene diisocyanate-based polyisocyanate.
[0081] The materials and weight fractions of each component in this example are shown in Table 1 and Table 2.
[0082] Example 2 to Example 10
[0083] Embodiments 2 to 10 provide a coating, respectively, which includes modified epoxy acrylate, aromatic polyurethane acrylate, photoinitiator, functional monomer, defoamer, dispersant, anti-settling agent, filler and curing agent, wherein the modified epoxy acrylate, aromatic polyurethane acrylate, photoinitiator, defoamer, dispersant, anti-settling agent, filler and curing agent are the same as those in Embodiment 1, and the functional monomer includes at least one of tripropylene glycol diacrylate, hydroxyethyl methacrylate and dipropylene glycol diacrylate, as shown in Table 1 and Table 2. The materials and mass fractions of each component in these coatings are shown in Table 1 and Table 2.
[0084] Comparative Examples 1 to 9
[0085] Comparative Examples 1 to 9 provide a coating, respectively, and the materials and mass fractions of the components in the coatings are shown in Tables 1 and 2. Among them, the main resin in Comparative Example 9 is a standard epoxy acrylate that has not been modified, and does not contain the adipic acid-modified epoxy acrylate in Example 1.
[0086] Table 1
[0087]
[0088]
[0089] The source manufacturers and ingredients of the components in Examples 1-10 and Comparative Examples 1-9 in Table 1 above are shown in Table 2.
[0090] Table 2
[0091]
[0092] Performance Testing
[0093] The coatings of Examples 1 to 10 and Comparative Examples 1 to 9 were tested for appearance and viscosity. The appearance of the coatings of Examples 1 to 10 and Comparative Examples 1 to 9 was a milky white viscous liquid, and the viscosity was shown in Table 3.
[0094] The coatings of Examples 1 to 10 and Comparative Examples 1 to 9 were used to test the adhesion of the coatings on the pine wood substrate using the GB / T 9286 standard. The results are shown in Table 3.
[0095] The coatings of Examples 1 to 10 and Comparative Examples 1 to 9 were applied to pine wood substrates, and then respectively heated at 60 mj / cm 2 、80mj / cm 2 、100mj / cm 2 、120mj / cm 2 、150mj / cm 2 After curing under UV lamp energy, the coating was subjected to hot and cold cycle treatment in the manner of -20°C, 2h, 80°C, 2h, repeated ten times, and the state of the coating at the knot of the pine wood substrate was observed. The results are shown in Table 3.
[0096] Table 3
[0097]
[0098]
[0099] As shown in Table 3, the coatings of Examples 1 to 10 do not add organic solvents, have low VOC emissions during the coating process, have viscosities of 87 to 120 KU (25° C.), have good fluidity, and can be coated on pine substrates with a roller coater when in use. The activation period of these coatings is greater than or equal to 24 hours, so that the coatings can be better expanded and leveled on the surface of the pine substrate, and the coatings can be better combined with the pine substrate, thereby further improving the adhesion and oil sealing effect, while reducing the coating problems caused by insufficient time, and further improving the working efficiency of the coating production line.
[0100] The adhesion of the coatings provided by Examples 1 to 10 is all level 2, with good adhesion, which is significantly better than the adhesion of the coatings provided by Comparative Examples 1 to 9.
[0101] In addition, the coatings of Examples 1 to 10 have low curing energy and are not easily cured when the UV lamp energy is 80-100 mj / cm 2When the coating is cured and subjected to a hot and cold cycle, there is no blistering or shedding at the junction of the pine wood substrate. The coating provided in the embodiment of the present application is compounded with modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent, so that the coating has the advantages of excellent adhesion, long activation period, fast curing speed, good adhesion to pine wood substrate, excellent oil sealing effect and low VOC emission.
[0102] The curing energy of the coatings of Examples 1 to 10 is 80-100 mj / cm 2 When the curing energy is 60mj / cm 2 , 120-150mj / cm 2 When the UV lamp energy is 120-150mj / cm 2 When the coating is cured by UV light, the temperature of the pine wood substrate rises, causing the grease to seep out of the pine knots, so that the adhesion of the coating film at the knots becomes poor, falls off or bubbles. When the UV lamp energy is 80-100mj / cm 2 During coating, the temperature rise of the pine wood substrate is low, which is not enough to cause the oil to seep out of the pine knots, thus avoiding the deterioration of coating adhesion, falling off or bubbling at the knots.
[0103] Compared with Example 2, the coating of Comparative Example 1 has a lower content of HM-303, and the curing energy of the coating of Comparative Example 1 is 60-150mj / cm 2 When the curing energy is 80-100 mj / cm 2 When the temperature is high, the adhesion is level 2, and there is no shedding or bubbling at the junction after hot and cold cycles, indicating that the adhesion and hot and cold cycle performance are affected by HM-303 and curing energy.
[0104] The main difference between the coating of comparative example 2 and the coating of example 1 is that the coating of comparative example 2 has a higher content of HM-303. The curing energy in comparative example 2 is 60-150 mj / cm 2 When the curing energy is 80-100 mj / cm 2 When the adhesion is level 2, and there is no shedding and blistering of the coating film at the junction after the hot and cold cycle. HM-303 has a brittle structure and large shrinkage, so the mass fraction of HM-303 in the coating is controlled to 40-50 parts, or the mass content of HM-303 is controlled to 40-50%, so that HM-303 is compounded with other components, thereby further improving the adhesion and hot and cold cycle stability of the coating.
[0105] The mass fraction of the coating 5210 in Comparative Example 3 is 20 parts (mass content is 20%), which is higher than the content of 5210 in the coating of Example 1. The curing energy of the coating in Comparative Example 3 is 60-150 mj / cm 2 When the adhesion at the stutter is level 3, and the coating at the stutter falls off or bubbles after the hot and cold cycles, the adhesion and hot and cold cycle stability of the coating in Comparative Example 3 are lower than those in Example 1. This shows that the mass fraction of 5210 in the coating is controlled to be less than or equal to 15 parts, or the mass content of 5210 is controlled to be less than or equal to 15%, so that 5210 is compounded with other components in the coating, which effectively improves the adhesion of the coating to the pine wood substrate.
[0106] The main difference between the coating of comparative example 4 and the coating of examples 3 and 4 is the content of HEMA. The content of HEMA in the coating of comparative example 4 is higher than that in the coating of examples 3 and 4. The curing energy of the coating of comparative example 4 is 60-150 mj / cm 2 When the coating film adhesion is 4, the coating film falls off or bubbles at the junction after hot and cold cycles. This shows that HEMA affects the curing of the coating. Increasing the amount of HEMA added slows down the curing speed of the coating film, resulting in poor adhesion and hot and cold cycle performance.
[0107] The main difference between Comparative Example 8 and Examples 3, 8 and 9 is that the functional monomer EM231 in Comparative Example 8 is a trifunctional monomer with high viscosity, while the functional monomers EM222 or EN223 in Examples 3, 8 and 9 are bifunctional monomers. The coating film of Comparative Example 8 has a grade 4 adhesion, and the addition of EM231 makes the coating film brittle and shrinks greatly, resulting in poor adhesion, while the EM222 or EN223 monomer solution has a moderate coating film structure and shrinkage, and a grade 2 adhesion.
[0108] The functional monomer is controlled to include at least one of dipropylene glycol diacrylate, tripropylene glycol diacrylate and hydroxyethyl methacrylate, and the mass fraction of hydroxyethyl methacrylate is controlled to be less than or equal to 5 parts, or the mass content of hydroxyethyl methacrylate is controlled to be less than or equal to 5%, so that the functional monomer is compounded with other components, so that the coating film has a suitable structure and shrinkage, and the adhesion of the coating is effectively improved.
[0109] The main difference between the coating of comparative example 5 and the coating of examples 2 and 5 is the different content of curing agent. The mass fraction of curing agent WANNATE HT-100 in the coating of comparative example 5 is 15, which is higher than the mass fraction of curing agent in the coating of examples 2 and 5. The activation period of the coating of comparative example 5 is significantly reduced, indicating that the greater the amount of curing agent WANNATE HT-100 added, the shorter the activation period. The main reason is that the NCO group in WANNATE HT-100 will react with -OH and -COOH in the water in the air and the UV roller coating pine wood oil seal base coating, and the greater the amount of WANNATE HT-100, the faster the reaction, causing the coating viscosity to increase and gel. Therefore, the mass fraction of the curing agent is controlled within the range of 5 to 10 parts or the mass content is controlled within the range of 5 to 10%, so that the coating has good oil sealing effect, adhesion and cold and hot cycle stability, and at the same time, the coating has a longer activation period.
[0110] Comparing the coatings of Comparative Example 6 and Comparative Example 7 with the coating of Example 6, the main difference is that the mass fraction of JRCure 1103 in the coating of Comparative Example 6 is lower than that in the coating of Example 6, and the content of JRCure 1109 in Comparative Example 7 is lower than that in the coating of Example 6. The curing energy of the coating of Comparative Example 6 is 80-100 mj / cm 2 When the adhesion at the junction is 4, and the coating film bubbles at the junction of the hot and cold cycle, indicating that the reduction in the amount of JRCure 1103 added slows down the curing of the UV roller-coated pine wood sealer, resulting in poor overall coating performance. The curing energy of the coating in comparative example 7 is 80-100mj / cm 2 When the coating is dried, the adhesion of the coating at the junction is level 3, and the coating at the junction of the hot and cold cycle is bubbling. JRCure 1109 can promote the deep curing of the coating. When the amount of JRCure 1109 is reduced, the deep curing of the coating slows down, resulting in poor adhesion and hot and cold cycle of the coating at the junction. By controlling the mass fraction of the surface drying photoinitiator A (JRCure 1103) and the photoinitiator B (JRCure 1109) that promotes internal drying, the photoinitiator A and the photoinitiator B can enhance each other, so that when the coating is cured, the surface and the inside of the coating are evenly dried, further improving the uniformity and adhesion of the coating.
[0111] Comparing the coating of Comparative Example 9 with the coating of Example 1, the main difference is that the coating of Comparative Example 9 uses unmodified standard epoxy acrylate SM6105-100 as the main resin, and no hexadimethoxy-modified epoxy acrylate resin is added, while the coating of Example 1 uses hexadimethoxy-modified epoxy acrylate resin HM-303 as the main resin. The activation period of the coating of Comparative Example 9 is ≤2 hours, and the curing energy is 80-100mj / cm 2When the coating adhesion is level 4, the coating has blistering at the junction of the hot and cold cycles. Since SM6105-100 contains a certain amount of epoxy groups, and the epoxy groups and -NCO cure quickly, the activation period of the coating of Example 9 is greatly shortened. The hexadimethoxy-modified epoxy acrylic resin in Example 1 contains a certain amount of carboxyl groups, but no residual epoxy groups. The carboxyl groups react very slowly with -NCO, and can react with -OH in wood fibers to improve adhesion, so that the coating of Example 1 has a long activation period and high adhesion.
[0112] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A coating, characterized in that: The composition comprises the following components in parts by weight: 40-50 parts of modified epoxy acrylate; 10-15 parts of aromatic polyurethane acrylate; 16~36 parts of functional monomer; 3.2~5.4 parts of photoinitiator; 5~10 parts of curing agent; Wherein, the modified epoxy acrylate includes Jiangxi Kunlong HM-303, the functional monomer includes at least one of dipropylene glycol diacrylate and tripropylene glycol diacrylate, and the aromatic polyurethane acrylate includes at least one of Ketian Chemical 5210 and Jiangxi Kunlong HM316; The functional monomer further includes hydroxyethyl methacrylate, and the mass fraction of the hydroxyethyl methacrylate is less than or equal to 5 parts.
2. The coating according to claim 1, characterized in that The photoinitiator comprises a photoinitiator A and a photoinitiator B, wherein the photoinitiator A comprises at least one of 2-hydroxy-methylphenylpropane-1-one and 1-hydroxycyclohexyl phenyl ketone, and the photoinitiator B comprises bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.
3. The coating according to claim 2, characterized in that The mass fraction of the photoinitiator A is 3 to 5 parts; and / or The mass fraction of the photoinitiator B is 0.2-0.4 parts.
4. The coating according to any one of claims 1 to 3, characterized in that The curing agent includes an isocyanate curing agent.
5. The coating according to claim 4, characterized in that The curing agent includes hexamethylene diisocyanate-based polyisocyanate.
6. The coating according to any one of claims 1 to 3 and 5, characterized in that: The coating further comprises at least one auxiliary agent selected from the group consisting of (1) to (4): (1) 0.1~0.2 parts by mass of defoaming agent; (2) 0.2-0.5 parts by weight of dispersant; (3) 0.3~0.5 parts by weight of anti-settling agent; (4) 10 to 20 parts by weight of filler.
7. The coating according to claim 6, characterized in that: The defoaming agent comprises AIREX 920; and / or The dispersant comprises BYK 110; and / or The anti-settling agent comprises at least one of silicon dioxide and AEROSIL R972; and / or The filler includes at least one of talc, titanium oxide, aluminum oxide and calcium silicate.
8. The coating according to any one of claims 1 to 3, 5 and 7, characterized in that: The coating has an adhesion grade of 1-2; and / or At 25°C, the coating has a viscosity of 80-120 KU; and / or The curing energy of the coating is 80-100 mj / cm 2 ; and / or The activation period of the coating is ≥24 hours.
9. A method for preparing the coating according to any one of claims 1 to 8, comprising the following steps: Provide modified epoxy acrylates, aromatic polyurethane acrylates, functional monomers, photoinitiators and curing agents; Mixing materials including the modified epoxy acrylate, aromatic polyurethane acrylate, functional monomer, photoinitiator and curing agent to obtain a coating; in, The modified epoxy acrylate is 40-50 parts by weight, the aromatic polyurethane acrylate is 10-15 parts by weight, the functional monomer is 16-36 parts by weight, the photoinitiator is 3.2-5.4 parts by weight, and the curing agent is 5-10 parts by weight; The modified epoxy acrylate includes Jiangxi Kunlong HM-303; The functional monomer includes at least one of dipropylene glycol diacrylate and tripropylene glycol diacrylate, and the functional monomer also includes hydroxyethyl methacrylate, and the mass fraction of the hydroxyethyl methacrylate is less than or equal to 5 parts; The aromatic polyurethane acrylate includes at least one of Ketian Chemical 5210 and Jiangxi Kunlong HM316.
Citation Information
Patent Citations
Improved UVLED light curing paint
CN108485480A
Preparation method of wear-resistant high-adhesive-force solid wood floor
CN112974189A
Reciprocating spraying UV-LED curing adhesion primer and preparation method thereof
CN113621302A
UV mercury lamp light source cured pine oil sealing primer and preparation method thereof
CN115960500A